SCAI/CCAS/SPA Expert Consensus Statement for Anesthesia and Sedation Practice: Recommendations for Patients Undergoing Diagnostic and Therapeutic Procedures in the Pediatric and Congenital Cardiac Catheterization Laboratory. (November 2016) - Odegard, Kirsten C.; Vincent, Robert; Baijal, Rahul G.; Daves, Suanne M.; Gray, Robert G.; Javois, Alexander J.; Love, Barry A.; Moore, Philip; Nykanen, David; Riegger, Lori Q.; Walker, Scott G.; Wilson, Elizabeth C.
Abstract : Current practice of sedation and anesthesia for patients undergoing pediatric and congenital cardiac catheterization laboratory (PCCCL) procedures is known to vary among institutions, a multi-society expert panel with representatives from the Congenital Heart Disease Council of the Society for Cardiovascular Angiography and Interventions, the Society for Pediatric Anesthesia and the Congenital Cardiac Anesthesia Society was convened to evaluate the types of sedation and personnel necessary for procedures performed in the PCCCL. The goal of this panel was to provide practitioners and institutions performing these procedures with guidance consistent with national standards and to provide clinicians and institutions with consensus-based recommendations and the supporting references to encourage their application in quality improvement programs. Recommendations can neither encompass all clinical circumstances nor replace the judgment of individual clinicians in the management of each patient. The science of medicine is rooted in evidence, and the art of medicine is based on the application of this evidence to the individual patient. This expert consensus statement has adhered to these principles for optimal management of patients requiring sedation and anesthesia. What follows are recommendations for patient monitoring in the PCCCL regardless of whether minimal or no sedation is being used or general anesthesia is being provided by an anesthesiologist.